PERILAKU MENENTANG PROTOKOL KESEHATAN DIPENGARUHI OLEH TEORI KONSPIRASI VIRUS COVID-19 DITINJAU DENGAN TEORI INTERAKSIONISME SIMBOLIK - Raihan Akbar Khalil; Nurliana Cipta Apsari; Hetty Krisnani (Universitas Padjadjaran, 2021)
ABSTRACTConspiracy theory is a tendency to assume that a large event has been planned in secret by a powerful and evil entity, and acts simultaneously. lately, there are so many conspiracy theories in the world about covid-19 conspiracy theories, which can certainly cause a misinformation from the media to the general public, leading to violations of health protocols. Using symbolic interactionism theory, I wanted to analyze how behaviors opposing health protocols are influenced by viral conspiracy theories with symbolic interactionism theory. The method used is the study of literature, scientific literature, as well as credible sources. The result is that by believing the conspiracy theory covid-19 with various factors behind it such as age, education, income, and psychological condition. Narrative and persuasion communication styles can also influence some individuals to believe that the conspiracy theory is real. Some individuals commit violations of health protocols as a form of distrust they have. preventive measures that can be done is to conduct counseling on the importance of following health protocols, as well as regulation of the media regarding information that is not true existence.